2013
DOI: 10.3390/ijerph10083172
|View full text |Cite
|
Sign up to set email alerts
|

Linking Climate to Incidence of Zoonotic Cutaneous Leishmaniasis (L. major) in Pre-Saharan North Africa

Abstract: Shifts in surface climate may have changed the dynamic of zoonotic cutaneous leishmaniasis (ZCL) in the pre-Saharan zones of North Africa. Caused by Leishmania major, this form multiplies in the body of rodents serving as reservoirs of the disease. The parasite is then transmitted to human hosts by the bite of a Phlebotomine sand fly (Diptera: Psychodidae) that was previously fed by biting an infected reservoir. We examine the seasonal and interannual dynamics of the incidence of this ZCL as a function of surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
76
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 32 publications
(73 reference statements)
4
76
0
4
Order By: Relevance
“…A number of large-scale anthropogenic changes, such as land use and climate change, are contributing to the amplification of emerging infectious zoonotic diseases. For example, the distribution of vector species may shift or expand as a result of climate change, and lead to subsequent shifts in vector-borne disease burden (Bounoua et al, 2013;Ogden et al, 2008b). In the case of pathogens with complex transmission cycles involving multiple hosts and vector life stages, changing host ecology resulting from land use or environmental change may also alter human disease risk through vector abundance (Ogden et al, 2014), infection prevalence with the pathogen (Allan et al, 2003;Patz et al, 2004), or vector activity patterns (Ogden et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…A number of large-scale anthropogenic changes, such as land use and climate change, are contributing to the amplification of emerging infectious zoonotic diseases. For example, the distribution of vector species may shift or expand as a result of climate change, and lead to subsequent shifts in vector-borne disease burden (Bounoua et al, 2013;Ogden et al, 2008b). In the case of pathogens with complex transmission cycles involving multiple hosts and vector life stages, changing host ecology resulting from land use or environmental change may also alter human disease risk through vector abundance (Ogden et al, 2014), infection prevalence with the pathogen (Allan et al, 2003;Patz et al, 2004), or vector activity patterns (Ogden et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…The work of Kassem et al [25] in the Nile Delta revealed that sand fly densities were strongly correlated to temperature but not to relative humidity or wind velocity. However, the study of Bounoua et al [26] in Algeria demonstrated that the establishment of new endemic foci in regions that were not previously endemic was related to sufficient increase in minimum temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…To analyze some environmental variables related to disease incidence, geoprocessing is becoming very important for landscape epidemiology (Hugh‐Jones , Washino and Wood , Beck et al The transmission profile of leishmaniasis includes landscape elements and in Morocco, previous studies have suggested several environmental factors that may influence, directly or indirectly, the distribution of sand flies, including altitude (Guernaoui et al biotopes (Guernaoui and Boumezzough ), aspect (Boussaa et al climate (Rispail et al Bounoua et al and soil type (Boussaa and Boumezzough ).…”
Section: Introductionmentioning
confidence: 99%